2016
DOI: 10.1073/pnas.1524213113
|View full text |Cite
|
Sign up to set email alerts
|

A critical role for alternative polyadenylation factor CPSF6 in targeting HIV-1 integration to transcriptionally active chromatin

Abstract: Integration is vital to retroviral replication and influences the establishment of the latent HIV reservoir. HIV-1 integration favors active genes, which is in part determined by the interaction between integrase and lens epithelium-derived growth factor (LEDGF)/p75. Because gene targeting remains significantly enriched, relative to random in LEDGF/p75 deficient cells, other host factors likely contribute to gene-tropic integration. Nucleoporins 153 and 358, which bind HIV-1 capsid, play comparatively minor ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
345
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(382 citation statements)
references
References 62 publications
(81 reference statements)
34
345
1
2
Order By: Relevance
“…As previously reported (40,41,51), CPSF6 depletion by itself did not largely affect HIV-1 infection, with an ϳ20% increase in WT virus infectivity being observed. However, we found that CPSF6 depletion counteracted the triphasic dose-response curve of the drug against the WT virus ( Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As previously reported (40,41,51), CPSF6 depletion by itself did not largely affect HIV-1 infection, with an ϳ20% increase in WT virus infectivity being observed. However, we found that CPSF6 depletion counteracted the triphasic dose-response curve of the drug against the WT virus ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…Dulbecco modified Eagle medium (DMEM; Cellgro) supplemented with 10% fetal bovine serum (FBS; Cellgro) and 1ϫ penicillin-streptomycin (Pen-Str; Cellgro) was used to culture adherent cell lines. CPSF6 knockout HEK293T cells that carry an empty expression vector or express the 551-amino-acid isoform of CPSF6 (CPSF6[551]) were described previously (41). RPMI medium (Cellgro) supplemented with 10% FBS (Sigma), 1ϫ Pen-Str and 2 mM 2-glutamine (Cellgro) was used to culture an immortalized T cell line (MT4).…”
Section: Methodsmentioning
confidence: 99%
“…Table S2. HIV-1 and MLV integration sites in HEK293T cells alongside the matched random control simulated data were from published work (11). HT1080, HEK293T, MRC5, or HepG2 cell line-specific gene-expression activity was reported previously (GEO accession codes GSE58968, GSE11892, GSE63577, and GSE87958) (54)(55)(56)(57).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies uncovered a hierarchical mechanism that depends on HIV-1 capsid, the major viral structural protein (a product of the viral gag gene), and integrase, which interact with cellular proteins CPSF6 and LEDGF/p75, respectively (6)(7)(8)(9)(10)(11). Ablation of the mRNA maturation factor CPSF6 results in the bulk of virus abandoning generich domains, whereas ablation of the transcriptional coactivator LEDGF leads to a reduction of integration into transcription units while largely preserving the virus's ability to locate gene-rich domains (11). Thus, the capsid-CPSF6 and integrase-LEDGF axes appear to direct HIV-1 integration on the global and local scale, respectively.…”
mentioning
confidence: 99%
“…SupT1 and CEM-SS cells were propagated in similarly supplemented RPMI 1640 medium. Viruses used for infectivity measures and transmission electron microscopy were generated by plasmid DNA transfection of HEK293T cells as previously described (58).…”
Section: Methodsmentioning
confidence: 99%